Pengaruh Kebijakan Pemerintah Dan Harga Pada Keputusan Pembelian Jasa Penyelenggara Kursus Dengan Iklan Sosial Media Sebagai Variabel Mediasi Pada Lembaga Kursus Texas College Kota Metro - Riyanto, Kuncoro Budi; Rahayu, Sri Retnaning; Bahtiar, Hafidz (Universitas Muhammadiyah Metro, 2023)
The research is motivated by the fact that the number of new students enrolling at the TexasCollege course has experienced ups and downs from 2018 to 2021 due to rising prices foreach level of course over the last four years. If this goes on continuously it will have an impacton student interest. The purpose of this study was to determine the effect of government policyand prices on purchasing decisions for course provider services with social media advertisingas a mediating variable at the Texas College Metro Course Institute. This research isquantitative research. With this type of explanatory survey research, the sample determinationtechnique was purposive sampling, as many as 75 students from LKP Texas College Metro. Asa measuring tool, 80 questionnaire items were used with Likert scale measurements andanalyzed using Path Analysis. The results of the study show that government policies have apositive effect on service purchasing decisions. Price has a positive effect on the decision topurchase services. Social media advertising has a positive effect on service purchasingdecisions. Government policies have a positive effect on social media advertising. Price has apositive effect on social advertising. Government policies have a positive effect on servicepurchasing decisions through the mediation of social media advertising. Price has a positiveeffect on service purchasing decisions through the mediation of social media advertising.